Reason to Believe : Cultural Agency in Latin American Evangelicalism - Smilde, David (Book collections on Project MUSE., 2007)
Based on fieldwork among Pentecostal men in Caracas, Venezuela, this ethnography seeks an explanation for the explosion of Evangelical Protestantism, unraveling the cultural and personal dynamics of Evangelical conversion to show how and why these men make the choice to convert, and how they come to have faith in a new system of beliefs.